Media Analysis of News Articles During COVID-19: Renewal, Continuity and Cultural Dimensions of Creative Action - Mattson, David; Mathew, Katie; Katz-Buonincontro, Jen (Frontiers in Psychology, 2021)
Worldwide, the COVID-19 pandemic has forced people to adapt quickly, and to reexamine interactions and responsibilities toward communities in creative ways. This paper presents a qualitative media analysis (Altheide and Schneider, 2013) of 50 online news articles (Los Angeles Times and New York Times) published between March 17th and August 6th, 2020 using the key-words “creativity” and “COVID-19.” Informed by a definition of creativity as actions that are considered both “new” and “appropriate” (Sternberg and Lubart, 1999), articles describing a “creative action” were kept for analysis. These articles highlight creative responses to the COVID-19 quarantine in various domains including architecture, fashion, and faith. In this paper, we discuss the themes derived during this analysis- “renewal and continuity” and “the multidimensionality of creativity” which elaborate and contextualize a perspective of socio-cultural creativity theory and propose two implications of this study. The first implication posits that creativity was an observable, cultural response to the COVID-19 pandemic. The second implication offers a broader concept of how cultural resources function as dynamic constraints or “affordances” within the Five A’s model of creativity (Glǎveanu, 2013). Discussion of further research through the lens of socio-cultural creativity is discussed.